Comparison of Urodynamics and Perineal Ultrasonography for the Diagnosis of Mixed Urinary Incontinence in Women. (2nd April 2018) - Hu, Yang; Lou, Yelin; Liao, Limin; Xu, Min; Zhang, Heng; Yang, Qing; Wu, Haixiao
Abstract : Objectives: This study aimed to compare urodynamic studies (UDS) and perineal ultrasonography (US) for the assessment of mixed urinary incontinence (MUI) in women in China. Methods: Adult women with MUI and healthy control participants were enrolled from 2 centers in China (Zhejiang and Beijing) between September 2010 and April 2017. Baseline clinical characteristics were recorded. The MUI type was categorized by the King's Health Questionnaire: stress‐predominant, urge‐predominant, or equal predominance. Urodynamic studies were performed, followed within 1 week by perineal US. Tolerability of the investigations was compared by a 3‐point scale: better than, worse than, or equal to. Results: For UDS parameters, compared with controls, the urge‐predominant MUI group had a lower maximal flow rate, smaller bladder volume, higher detrusor pressure at urethral opening, higher detrusor pressure at maximal flow, and higher incidence of detrusor overactivity; the stress‐predominant MUI group had a lower maximal urethral closure pressure and functional urethral length; and the equal MUI group had a higher detrusor pressure at maximal flow and lower maximal urethral closure pressure ( P  < .05). For US parameters, compared with controls, the stress‐predominant MUI group had a greater dynamic posterior urethral angle, dynamic angle of urethral inclination, descent of the bladder neck, and dynamic pubourethral distance; the urge‐predominant MUI group had a greater detrusor thickness; and the equal MUI group had a greater descent of the bladder neck ( P  < .05). All UDS and US parameters differed significantly between the stress‐predominant and urge‐predominant groups ( P  < .05). The dynamic angle of urethral inclination, descent of the bladder neck, and dynamic pubourethral distance were inversely correlated with detrusor pressure at maximal flow and functional urethral length, while detrusor wall thickness was positively correlated with detrusor pressure at maximal flow and functional urethral length. Perineal US was better tolerated than UDS. Conclusions: Perineal US parameters show good correlations with UDS parameters. Ultrasonography is better tolerated than UDS and provides additional morphologic data. Perineal US could facilitate the diagnosis of urge‐predominant MUI.